Perancangan Sistem Informasi Akuntansi Belanja Pegawai Aparatur Desa Berbasis Web Menggunakan PHP dan MySQL - Sasqia Dwicky Ambarputri Hendarsyah (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2020)
This research is an experimental stuudy because as it is known that government agencies have been simultaneously using application provided by the central government itself. But not a few employees who feel difficulties in operating the application. Research conducted a survey with complaints that the application is not as easy as imagined and therefore research intend to make the application more user friendly. The purpose of this study aims to design an application of web-based employee accounting apparatus vilage web-based applucation using PHP and MySQL. The resesarch method used in designing a web-bassed employee apparatus accounting information system using PHP and MySQL is to use a survey method that is to obtain data from the results of the visit. Information sysrems are already needed in this era, among other to help financial reporting process honestly and get accurate values in accordance with applicable accounting standards. As has been expalined in order to make it easier in the operation process the accounting information system that is user friendly is needed and for it’s use itself is in accordance with the user’s whished so that various problems encountered during using the information system that prvioously could be overcome so that it would be easier to understand in it’s use. Therefore the accounting information system for employee expenditure on the village apparatus web-based uses PHP and MySQL so that it is more easily understood by the user. Keywords: Accounting Information Systems,Village Personel Expenditure